2008
DOI: 10.1124/pr.107.00107
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drugs: Comparison in Animal Models of Efficacy, Neurotransmitter Regulation, and Neuroprotection

Abstract: Various lines of evidence indicate the presence of progressive pathophysiological processes occurring within the brains of patients with schizophrenia. By modulating chemical neurotransmission, anti-psychotic drugs may influence a variety of functions regulating neuronal resilience and viability and have the potential for neuroprotection. This article reviews the current literature describing preclinical and clinical studies that evaluate the efficacy of antipsychotic drugs, their mechanism of action and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
179
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(182 citation statements)
references
References 611 publications
(765 reference statements)
1
179
0
2
Order By: Relevance
“…Hyperdopaminergia, a well-accepted model of psychosis, is known to induce hyperlocomotion and disrupt prepulse inhibition (PPI), whereas inhibition of the DA system by haloperidol induces catalepsy in mice (19). Inhibition of hyperlocomotion, reversal of disrupted PPI, and cataleptic potential are commonly used behavioral tests in rodents to assess efficacy of antipsychotics (19,20). We therefore sought to delineate the effect of neuronalspecific deletion of GSK3β on hyperlocomotion, PPI, and haloperidol (HAL)-induced catalepsy.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperdopaminergia, a well-accepted model of psychosis, is known to induce hyperlocomotion and disrupt prepulse inhibition (PPI), whereas inhibition of the DA system by haloperidol induces catalepsy in mice (19). Inhibition of hyperlocomotion, reversal of disrupted PPI, and cataleptic potential are commonly used behavioral tests in rodents to assess efficacy of antipsychotics (19,20). We therefore sought to delineate the effect of neuronalspecific deletion of GSK3β on hyperlocomotion, PPI, and haloperidol (HAL)-induced catalepsy.…”
Section: Resultsmentioning
confidence: 99%
“…One of the key neural sites of antipsychotic action is the nucleus accumbens shell (Deutch et al, 1992;Robertson et al, 1994;Semba et al, 1999) as both typical and atypical antipsychotic drug induce c-Fos expression in this brain region. These effects have been related to the therapeutic properties of antipsychotic drugs (Lieberman et al, 2008;Robertson et al, 1994). More recently, the prefrontal cortex has been identified as another brain subregion area that may be involved in antipsychotic efficacy (Wadenberg et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A new generation of antipsychotic drugs, the atypical antipsychotics (for example quetiapine, olanzapine, risperidone and clozapine), with a lower affinity and occupancy for the dopaminergic receptors, but an additional occupancy for the serotoninergic 5-HT 2A and other receptors [8] have become available. Antipsychotics are effective in reducing the severity of positive psychotic symptoms but have limited impact on negative symptoms, cognitive impairment and produce a range of side effects including extra-pyramidal symptoms, prolactin elevation, sedation and cardio-metabolic effects [7]. Compared to typical antipsychotics, atypical antipsychotics induce less extra-pyramidal adverse effects and more metabolic adverse *Address correspondence to this author at the Psychiatric Outpatient Department, Medical Image Analysis Centre, Petersgraben 4, CH-4031 Basel, Switzerland; Tel: 0041613286126; Fax: 0041612654588; E-mail: sborgwardt@uhbs.ch effects [7] but the underlying neurobiological mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of neuroimaging studies have reported that as the illness proceeds, patients rapidly lose cerebral gray matter (GM), particularly in the frontal, temporal and limbic lobes [3,4]. The treatment of schizophrenia involves the use of antipsychotic drugs (typical antipsychotics, such as haloperidol), which act as antagonists at central dopamine D 2 receptors [5,6], although some of them have additional effects on other receptors [7]. A new generation of antipsychotic drugs, the atypical antipsychotics (for example quetiapine, olanzapine, risperidone and clozapine), with a lower affinity and occupancy for the dopaminergic receptors, but an additional occupancy for the serotoninergic 5-HT 2A and other receptors [8] have become available.…”
Section: Introductionmentioning
confidence: 99%